2016
DOI: 10.2320/jinstmet.j2016005
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a Ni-Al Intermetallic compound Layer by AIH-FPP Treatment

Abstract: In order to form a Ni Al intermetallic compound layer on a carbon steel surface, Atmospheric controlled Induction Heating Fine Particle Peening (AIH FPP) was carried out at 900°C in argon atmosphere with nickel and aluminum particles mechanically milled by planetary ball mills. The treated surface was analyzed using a scanning electron microscope (SEM), an energy dispersive X ray spectrometer (EDX), and an X ray diffraction (XRD). Oxidation tests were carried out at 900°C for 100 hours. Results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
4
0
1
Order By: Relevance
“…Ti-Al 金属間化合物は,軽量で耐食性や耐摩耗性に加えて 耐熱性にも優れるため,高温構造材料としての利用が期待さ れている.実際,自動車のターボチャージャーなどの素材と して最近利用され始めている.しかし,靱性や延性に乏しく 脆いという欠点を有しているため,バルク材を部品形状に機 械加工して利用することは困難である.そこでこの金属間化 合物を,靱性の高い基材へコーティングすることで,その優 れた特性を最大限に活かす試み 1,2) が検討されている. 本研究では,この金属間化合物を鋼の表面に被覆する手法 として,著者らが開発した AIH-FPP (Atmospheric controlled Induction Heating Fine Particle Peening) 処理 [3][4][5][6][7][8][9][10][11][12][13][14] に着目した.…”
unclassified
“…Ti-Al 金属間化合物は,軽量で耐食性や耐摩耗性に加えて 耐熱性にも優れるため,高温構造材料としての利用が期待さ れている.実際,自動車のターボチャージャーなどの素材と して最近利用され始めている.しかし,靱性や延性に乏しく 脆いという欠点を有しているため,バルク材を部品形状に機 械加工して利用することは困難である.そこでこの金属間化 合物を,靱性の高い基材へコーティングすることで,その優 れた特性を最大限に活かす試み 1,2) が検討されている. 本研究では,この金属間化合物を鋼の表面に被覆する手法 として,著者らが開発した AIH-FPP (Atmospheric controlled Induction Heating Fine Particle Peening) 処理 [3][4][5][6][7][8][9][10][11][12][13][14] に着目した.…”
unclassified
“…In AIH-FPP, an induction-heated metal is subjected to fine particle peening (FPP) under an arbitrary atmosphere. Layers containing intermetallic compounds such as Ni-Al 10) and Ti-Al [11][12][13][14] without non-reacted metallic elements can be formed on the surfaces of the carbon steel 10,11) or titanium alloy [12][13][14] within a few minutes. The modified layers improve the wear resistance and high-temperature oxidation resistance of the substrates.…”
Section: Introductionmentioning
confidence: 99%
“…The modified layers improve the wear resistance and high-temperature oxidation resistance of the substrates. 10,11,13) Possible mechanisms for the rapid formation of the intermetallic compound layer include the occurrence of combustion synthesis reactions between the elements of the shot particles and substrate 13) or diffusion of the shot particle elements transferred to the surface into the substrate. 14) Based on the previous studies, the application of AIH-FPP with shot particles containing aluminum is expected to form an Fe-Al intermetallic compound layer on stainless steel surfaces rapidly, and the tribological properties of the steel would be improved.…”
Section: Introductionmentioning
confidence: 99%
“…6,7) Our work has recently shown that intermetallic compound layers can be produced on the surface of carbon steel by AIH-FPP treatment via a combustion synthesis reaction 8,9) that occurs on the surface of the treated material. 10,11) We have also proposed that mechanically-milled shot particles containing different elements could be used to create homogeneous intermetallic compound layers. 10) In previous work, intermetallic compound layers having a minimal concentration of voids were created on titanium alloy surfaces upon applying the AIH-FPP treatment, based on mechanically-milled pure titanium and aluminum particles mixed with nickel based alloy particles.…”
Section: Introductionmentioning
confidence: 99%
“…10,11) We have also proposed that mechanically-milled shot particles containing different elements could be used to create homogeneous intermetallic compound layers. 10) In previous work, intermetallic compound layers having a minimal concentration of voids were created on titanium alloy surfaces upon applying the AIH-FPP treatment, based on mechanically-milled pure titanium and aluminum particles mixed with nickel based alloy particles. 12) However, the resulting layers have not yet been analyzed in detail, and the effect of the intermetallic compound layer on the properties of titanium alloy has not been investigated.…”
Section: Introductionmentioning
confidence: 99%